(untitled) (Journal of Partial Differential Equations, 1992)
In this paper by using upper-lower solution method the critical wave speed of wave front for a simplified mathematical model of Belousov-Zhabotinskii chemical reaction u_t - u_xx = u(1 - u - rv) v_t - v_xx = -buv is obtained, where 0 < r < 1, b > 0 are known.